2002
DOI: 10.1093/condor/104.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of House Wren Nestlings Afflicted by Hematophagous Ectoparasites: A Test of the Parental Compensation Hypothesis

Abstract: This study asked whether parent House Wrens (Troglodytes aedon) in a Wyoming population increased rates of food delivery to broods parasitized by hematophagous blow fly larvae and mites. We observed no significant difference in rates at which pairs fed nestlings at nests with naturally heavy infestations of fly larvae (6–19 larvae per nestling) and nests in which nestling exposure to larvae was experimentally eliminated or severely reduced (0–2 larvae per nestling). The apparent failure of parents to compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Parasitized swallows and bluebirds did not effectively recover hemoglobin to nonparasitized levels, as found in other studies (Knutie et al, 2016;Morrison & Johnson, 2002;Råberg et al, 2007) (Table 3, Figure 3). Measuring micronuclei in red blood cells in the future would provide a proxy of whether any blood was recovered by the host .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Parasitized swallows and bluebirds did not effectively recover hemoglobin to nonparasitized levels, as found in other studies (Knutie et al, 2016;Morrison & Johnson, 2002;Råberg et al, 2007) (Table 3, Figure 3). Measuring micronuclei in red blood cells in the future would provide a proxy of whether any blood was recovered by the host .…”
Section: Discussionsupporting
confidence: 79%
“…Resistance mechanisms, such as mounting an immune response, can kill the parasite and therefore reduce the costs associated with parasite exposure, such as blood loss (Owen et al, 2010). Tolerance mechanisms, such as resource compensation or tissue repair, do not kill the parasite but instead allow the host to deal with greater parasite pressure (Christe, Richner, & Oppliger, 1996;Knutie et al, 2016;Medzhitov et al, 2012;Morrison & Johnson, 2002;Tripet & Richner, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on similar systems in North America involving hematophagous larvae of Protocalliphora spp. also failed to show a significant difference in parental food provisioning in relation to infestation, as for example, Eastern Bluebirds ( Sialia sialis ) infested by the blowfly Protocalliphora sialia (Grab et al 2019 ), or House Wrens ( Troglodytes aedon ) infested by Protocalliphora parorum (Morrison and Johnson 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, parental compensation via a higher food supply to nestlings, or other behaviors, will increase current reproductive effort, but at the expense of reducing residual reproductive value (Perrin et al 1996 ), a life-history trade-off experimentally demonstrated in many studies (e.g., Richner and Tripet 1999 ). Higher food provisioning allows nestlings to allocate more resources to blood and tissue replacement and growth (Mason 1944 ; Johnson and Albrecht 1993 ; Morrison and Johnson 2002 ). The extent of parental compensation may be influenced by environmental conditions and the amount or quality of available food (Tremblay et al 2005 ), among other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on host parental care in response to ectoparasites have tested the food compensation hypothesis, which predicts that parents will increase food delivery to offspring at parasitized nests to compensate for the nutritional and energetic costs of parasitism [15,16]. Evidence for the food compensation hypothesis has been mixed [17][18][19][20][21], perhaps due to sex differences in the value of current versus future broods [20].…”
Section: Introductionmentioning
confidence: 99%